Development of propolis powder for encapsulation via freeze drying method : extraction of propolis, components identification and an antioxidant activity study - Parvathi Nandini, Balah Krishnan (2018)
Propolis is an extracted product from bees wax which functions as protective barrier in bee hives. This study was conducted to overcome the problem of stickiness and gummy characteristic of propolis. The group objective was to develop propolis powder using freeze drying method. The individual objectives of conducting this research were to extract propolis by water and ethanol extraction method. Next aim was to determine components of propolis and evaluate its antioxidant activity. Propolis was extracted by using water and ethanol extraction method. The determination of propolis compounds for instances, polyphenol and flavonoids was carried out using UV Vis Spectrophotometer at different wavelengths. An antioxidant activity of propolis was also determined by evaluating degradation of DPPH and comparing with control. The ethanol extraction method produced more yield compared to water extraction method. In addition, total polyphenol and flavonoid content in ethanol extract of propolis (EEP) was proven to be much higher in comparison to water extract propolis (WEP). The antioxidant activity of EEP was observed to be higher than WEP as the degradation of DPPH chemical was faster in EEP than WEP. In a nutshell, ethanol extraction method produced EEP with higher polyphenol, flavonoid content and higher antioxidant activity than water extraction method.